Implementação de algoritmos de sistemas de antenas inteligentes - SOARES, Jabez de Souza (2018)
This work has as objective to study some aspects of the smart antennas' running and their arrays in a general way. One reason for that is that adaptive arrays can reduce the interference that strongly affects the performance of the system. Primarily it was made a resume of the general principles of antennas arrays and adaptation algorithms. Based on the principles, many possibilities of arrays are analyzed and the result of each variation in many arrays. Therefore, it is valued, by simulation, the array behavior’s are subject to some factors, naturals or not.